Toll-Like Receptor Signaling Drives Btk-Mediated Autoimmune Disease - Rip, Jasper; de Bruijn, Marjolein J. W.; Appelman, Marjolein K.; Pal Singh, Simar; Hendriks, Rudi W.; Corneth, Odilia B. J. (Frontiers in Immunology, 2019)
Bruton′s tyrosine kinase (Btk) is a signaling molecule involved in development and activation of B-cells through B-cell receptor (BCR) and Toll-like receptor (TLR) signaling. We have previously shown that transgenic mice that overexpress human Btk under the control of the CD19 promoter (CD19-hBtk) display spontaneous germinal center formation, increased cytokine production, anti-nuclear autoantibody formation and systemic autoimmune disease upon aging. As distorted TLR and BCR signaling are both implicated in autoimmune diseases, we studied the impact of TLR and BCR signaling on splenic B-cell characteristics. Using phosphoflow cytometry, we observed that phosphorylation of ribosomal protein S6, a downstream target of Akt, was increased in CD19-hBtk B cells following BCR stimulation, but decreased following TLR stimulation, when compared with wild-type B cells. Likewise, the CD19-hBtk transgene enhanced B cell survival and proliferation upon anti-IgM stimulation, but had an opposite effect following CpG or CpG/anti-IgM stimulation. In contrast, a synergistic effect of CpG and anti-IgM on the upregulation of the co-stimulatory molecule CD80 was specifically observed in CD19-hBtk B cells. In splenic follicular and marginal zone B cells from aging CD19-hBtk transgenic mice BCR signaling stimulated in vitro IL-10 production in synergy with TLR4 and particularly TLR9 stimulation, but not with TLR3 and TLR7. The enhanced capacity of CD19-hBtk follicular B cells to produce the pro-inflammatory cytokines IFN and IL-6 compared with wild-type B cells, was however not further increased upon in vitro BCR or TLR9 stimulation. Finally, we used crosses with mice deficient for the TLR-associated molecule myeloid differentiation primary response 88 (MyD88) to show that TLR signaling was crucial for spontaneous formation of germinal centers, increased production of IFN and IL-6 by B cells and the induction of anti-nuclear autoantibodies in CD19-hBtk mice. Taken together, we conclude that high Btk expression does not only increase B cell survival following BCR stimulation, but also renders B cells more sensitive to TLR stimulation, resulting in increased expression of CD80 and IL-10 in activated B cells. Although BCR-TLR interplay is complex, our findings show that both signaling pathways are crucial for the development of pathology in a Btk-dependent model for systemic autoimmune disease.